2010
DOI: 10.1016/j.ccr.2010.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Castrate-Recurrent Prostate Cancer by a Small-Molecule Inhibitor of the Amino-Terminus Domain of the Androgen Receptor

Abstract: Castration-recurrent prostate cancer (CRPC) is suspected to depend on androgen receptor (AR). The AF-1 region in the amino-terminal domain (NTD) of AR contains most, if not all, of the transcriptional activity. Here we identify EPI-001, a small molecule that blocked transactivation of the NTD and was specific for inhibition of AR without attenuating transcriptional activities of related steroid receptors. EPI-001 interacted with the AF-1 region, inhibited protein-protein interactions with AR, and reduced AR in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
497
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 460 publications
(514 citation statements)
references
References 54 publications
13
497
2
2
Order By: Relevance
“…4D) could be achieved. These levels of inhibition are similar to that of EPI-001, which could achieve ϳ80% inhibition of the AR(1-653) truncation mutant, lacking the LBD, when tested at 25 M concentration on PC3 cells co-transfected with ARR 3 tk-luciferase reporter (44).…”
Section: Discussionsupporting
confidence: 52%
“…4D) could be achieved. These levels of inhibition are similar to that of EPI-001, which could achieve ϳ80% inhibition of the AR(1-653) truncation mutant, lacking the LBD, when tested at 25 M concentration on PC3 cells co-transfected with ARR 3 tk-luciferase reporter (44).…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have shown that resveratrol, EPI-001, RD162, and MDV3100 also have the ability to inhibit both androgenindependent and androgen-dependent proliferation in prostate cancer cells (71,76,87). Resveratrol and EPI-001 have been shown to inhibit the growth of androgen-independent prostate cancer cells by negatively regulating PI3K/AKT pathway-activated AR activity.…”
Section: Discussionmentioning
confidence: 99%
“…12 In addition, tumors that are refractory to conventional androgen deprivation therapy are susceptible to more potent androgen pathway inhibitors. 13,14 These studies strongly indicate that AR signaling continues to play a significant role in CRPC. Thus, more comprehensive understanding of the regulation of the AR axis and the development of novel AR signaling-targeting therapies is imperative in this field.…”
Section: Introductionmentioning
confidence: 95%